Design Thinking in School Counseling: A New Model for Student-Centered Problem Solving in the Digital Age - Rina Farah; Aom Thai; Felipe Souza (PT. Sinergi Bersahaja Sejahtera, 2025)
Background. The increasing complexity of student needs in the digital age requires school counselors to adopt innovative approaches that move beyond traditional problem-solving frameworks. Design Thinking (DT), originally applied in business and technology, offers a human-centered and iterative process that emphasizes empathy, creativity, and collaboration, making it highly relevant for modern counseling practices. Purpose. This study aimed to develop and examine a student-centered counseling model based on Design Thinking. Specifically, it sought to investigate how DT principles—empathize, define, ideate, prototype, and test—can be systematically integrated into school counseling to enhance students’ problem-solving skills, emotional resilience, and engagement in a digital learning environment. Method. A qualitative design-based research approach was employed, involving 45 school counselors and 120 high school students across three urban schools. Data were collected through focus group discussions, reflective journals, and digital platform interactions, and were analyzed thematically to construct the proposed model. Results. The findings demonstrate that the integration of Design Thinking in counseling promotes higher student engagement, encourages collaborative exploration of solutions, and improves adaptability in addressing personal, academic, and socio-emotional challenges. Counselors reported that the DT model helped them better understand student perspectives, while students valued the iterative process that allowed them to test and refine their solutions. Conclusion. This study highlights the potential of Design Thinking as a transformative model for school counseling in the digital age. By shifting from counselor-centered to student-centered practices, DT provides a structured yet flexible framework that empowers students to become active participants in resolving their own problems, thus fostering autonomy and lifelong problem-solving skills.